2020
DOI: 10.1101/2020.11.23.395244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clonal dynamics in early human embryogenesis inferred from somatic mutation

Abstract: SummaryThe trillions of cells that constitute the human body are developed from a fertilized egg through embryogenesis. However, cellular dynamics and developmental outcomes of embryonic cells in humans remain to be largely unknown due to the technical and ethical challenges. Here, we explored whole-genomes of 334 single-cell expanded clones and targeted deep-sequences of 379 bulk tissues obtained from various anatomical locations from seven individuals. Using the discovered 1,688,652 somatic mutations as an i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 87 publications
1
14
0
Order By: Relevance
“…The increased relative portion of SBS1 in late-stage somatic mutations appears to represent active proliferation and clonal expansion during late-embryonic and post-natal or aging periods 22,23 . Although the etiologies associated with most indel signatures remain unknown, the higher contributions of ID1 and ID2 in early-stage SNVs and ID5 and ID8 in late-stage SNVs were consistent with a previous finding 24 .…”
supporting
confidence: 91%
“…The increased relative portion of SBS1 in late-stage somatic mutations appears to represent active proliferation and clonal expansion during late-embryonic and post-natal or aging periods 22,23 . Although the etiologies associated with most indel signatures remain unknown, the higher contributions of ID1 and ID2 in early-stage SNVs and ID5 and ID8 in late-stage SNVs were consistent with a previous finding 24 .…”
supporting
confidence: 91%
“…Mutation is considered as the only source to provide genetic variation, and has been extensively studied in fields like evolution, agriculture and human diseases, partially due to the relatively easy and large-scale identification and functional exploration by genome sequencing [15,[34][35][36][37][38]. As we found here, different mutation types and rates, and their combination with factors like effective population size, recombination and selection, do interfere with the dynamics of LD distribution.…”
Section: Discussionmentioning
confidence: 93%
“…It is not uncommon that mutations are indicated to be involved in the complex trait of importance, e.g. agriculture or human disease studies [15,[34][35][36][37][38]. Many questions remained to be answered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the levels of mosaicism may vary greatly in whole blood as a result of somatic clonal expansion, especially in subjects with advanced age [26]. Furthermore, recent work has shown that blood cell lineages branch off from other cell lineages early in embryogenesis, and that certain bottlenecks in embryonic development lead to heterogeneity in genetic mosaicism in different regions of the brain [27][28]. Thus, it has been suggested that somatic mosaicism may not be measured in the most accurate fashion through sampling whole blood samples.…”
Section: Introductionmentioning
confidence: 99%